A Textbook of Optics - Subrahmanyam, N. : Brij Lal : M. N. Avadhanulu; Lal, Brij (New Delhi : S. Chand, 1999)
Chemistry and Physics
Keywords: Optics; Lenses; Optical instruments; Light; Photometry; Diffraction; Polarization; Spectrum; Crystal structure; Atomic physics